2024
DOI: 10.1002/adma.202312027
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Insights into Cathode Calcination for Predictive Synthesis: Kinetic Crystallization of LiNiO2 from Hydroxides

Akhil Tayal,
Pallab Barai,
Hui Zhong
et al.

Abstract: Calcination is a solid‐state synthesis process widely deployed in battery cathode manufacturing. However, its inherent complexity associated with elusive intermediates hinders predictive synthesis of high‐performance cathode materials. Here, we use correlative in situ X‐ray absorption/scattering spectroscopy to investigate the calcination of nickel‐based cathodes, focusing specifically on LiNiO2 synthesized from hydroxides. By combining in situ observation with data‐driven analysis, we reveal concurrent lithia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…Formation of a layered Li 1– x NiO 2 ( x < 1) phase occurs at temperatures exceeding 436 °C, with further heating required to complete its lithiation. Several related studies have reported similar findings, in which LiOH begins to react with and lithiate NiO at temperatures ranging from 210 to 450 °C. ,, In contrast, Li 2 CO 3 does not react with the Ni precursor in appreciable amounts until the synthesis temperature exceeds 600 °C, likely due to the higher melting point of Li 2 CO 3 (723 °C) in comparison to LiOH (462 °C) . Increased reactivity at low temperature has also been reported when using LiOH to synthesize other cathode compositions. , These low temperatures not only diminish Ni Li antisite defects, but also provide improved control over product morphology at the expense of higher material costs and more processing challenges.…”
Section: The Role Of Precursor Selection In the Synthesis Of Battery ...supporting
confidence: 53%
“…Formation of a layered Li 1– x NiO 2 ( x < 1) phase occurs at temperatures exceeding 436 °C, with further heating required to complete its lithiation. Several related studies have reported similar findings, in which LiOH begins to react with and lithiate NiO at temperatures ranging from 210 to 450 °C. ,, In contrast, Li 2 CO 3 does not react with the Ni precursor in appreciable amounts until the synthesis temperature exceeds 600 °C, likely due to the higher melting point of Li 2 CO 3 (723 °C) in comparison to LiOH (462 °C) . Increased reactivity at low temperature has also been reported when using LiOH to synthesize other cathode compositions. , These low temperatures not only diminish Ni Li antisite defects, but also provide improved control over product morphology at the expense of higher material costs and more processing challenges.…”
Section: The Role Of Precursor Selection In the Synthesis Of Battery ...supporting
confidence: 53%